Document Type Confusion: An Evaluation of Publications in Turkish Librarianship and Information World Journals - Çakmak, Tolga; Kaya, Simge (Information World, 2025)
This study aims to analyse the accuracy and consistency of the document types of publications in Turkish Librarianship and Information World journals indexed in international bibliographic databases in the field of librarianship and information science in Türkiye. In this study, the accuracy and consistency analyses of publication document types were conducted using full texts, journal web pages, and records in international citation indexes (Web of Science and Scopus). In this study, a quantitative research approach was adopted, and the descriptive method was utilized. The findings indicated that the document types specified in the full texts of the publications in both journals exhibited inconsistencies with the journals’ web pages and the citation databases in which they were indexed. It has been determined that document types labelled differently from the full texts of publications in journals are predominantly Opinions and Letters to the Editor. These types are often erroneously labeled as Research Articles. In this regard, it is recommended that verification be carried out from multiple sources or original providers to ensure the accuracy of document types. However, including document types with equivalents in international databases in academic journal publication policies would significantly contribute to standardization and data integrity.